Virtual Mouse: Design and implementation of an accelerometer based wireless mouse - Aryan, Arghya Dev Biswas; Wasif, Md. Fahmid; Hasan, Md. Mahmudul (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.